2008
DOI: 10.1590/s0102-76382008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco que afetam as complicações da dissecação da veia safena na revascularização cirúrgica do miocárdio

Abstract: Fatores de risco que afetam as complicações da dissecação da veia safena na revascularização cirúrgica do miocárdioThe risk factors affecting the complications of saphenous vein graft harvesting in aortocoronary bypass surgery Abstract Objective: Problem of wound healing is commonly observed after coronary artery bypass graft procedures. Our aim is to determine the prevalence and the predictors of saphenous vein harvesting complication after coronary revascularization procedures.Methods: After institutional et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Diabetes, hyperlipidemia, obesity, female gender, advanced age, and peripheral vascular disease are known risk factors for wound healing disturbances after open GSV harvest [2, 14]. Research has however shown that particularly these high-risk patients benefit most from minimally invasive harvest techniques.…”
Section: Wound Healing Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes, hyperlipidemia, obesity, female gender, advanced age, and peripheral vascular disease are known risk factors for wound healing disturbances after open GSV harvest [2, 14]. Research has however shown that particularly these high-risk patients benefit most from minimally invasive harvest techniques.…”
Section: Wound Healing Disturbancesmentioning
confidence: 99%
“…Therefore 80% of the donor-site infections are diagnosed after discharge, for instance by the patients general physician or cardiologist. Furthermore wound complications are often found to be responsible for additional surgery, prolonged hospital stay, increased hospital costs, and in some cases permanent disability [1, 2]. …”
Section: Introductionmentioning
confidence: 99%